Operation of the parental modeled construction of prosocial behavior in adolescents - Balabanian, Cinthia (2022)
The objective of this study was to operationalize the parental modeled construct of prosocial behavior for its evaluation in adolescents. 358 adolescents from 12 to 18 years old participated (M = 14.66; SD = 1.71) of both sexes, from the province of Córdoba, Argentina. Different psychometric analyzes were performed from which it was observed that All items were discriminative and with a corrected homogeneity index ≥ .30. Internal consistency was adequate (FC = .91). The exploratory and confirmatory factor analyzes indicated a one-dimensional structure of the test, which explained 36% of the variance. The final scale was made up of 18 items that presented adequate psychometric functioning, allowing a valid and reliable evaluation of the construct.